2022
DOI: 10.1109/ojcas.2022.3207598
|View full text |Cite
|
Sign up to set email alerts
|

Peak-Power Aware Life-Time Reliability Improvement in Fault-Tolerant Mixed-Criticality Systems

Abstract: Mixed-Criticality Systems (MCSs) include tasks with multiple levels of criticality and different modes of operation. These systems bring benefits such as energy and resource saving while ensuring safe operation. However, management of available resources in order to achieve high utilization, low power consumption, and required reliability level is challenging in MCSs. In many cases, there is a trade-off between these goals. For instance, although using fault-tolerance techniques, such as replication, leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(211 reference statements)
0
2
0
Order By: Relevance
“…In modern scientific and technical literature, it is noted that in a positional binary number system (PBNS), it is almost impossible to significantly increase the reliability and speed of the CS [5]. At the same time, it is known that the CS of real-time data processing, which operates in the unposition number system in residual classes (RNS) has high computational capabilities from the point of view of improving the performance of the implementation of integer modular arithmetic operations [6,7]. It is known from the point of view of computer machine arithmetic, RNS has three basic properties [7][8][9]: independence, equitution and little discharge of residues whose combination determines the unposition number system into RNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In modern scientific and technical literature, it is noted that in a positional binary number system (PBNS), it is almost impossible to significantly increase the reliability and speed of the CS [5]. At the same time, it is known that the CS of real-time data processing, which operates in the unposition number system in residual classes (RNS) has high computational capabilities from the point of view of improving the performance of the implementation of integer modular arithmetic operations [6,7]. It is known from the point of view of computer machine arithmetic, RNS has three basic properties [7][8][9]: independence, equitution and little discharge of residues whose combination determines the unposition number system into RNS.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is known that the CS of real-time data processing, which operates in the unposition number system in residual classes (RNS) has high computational capabilities from the point of view of improving the performance of the implementation of integer modular arithmetic operations [6,7]. It is known from the point of view of computer machine arithmetic, RNS has three basic properties [7][8][9]: independence, equitution and little discharge of residues whose combination determines the unposition number system into RNS. The results of preliminary studies have shown that the use of listed properties can ensure improvement of the reliability of the CS based on the use of CS [10].…”
Section: Introductionmentioning
confidence: 99%